Effect of ground gear modification on bycatch of rays in mediterranean bottom trawl fishery. (15th May 2022) - Fakıoğlu, Y.E.; Özbilgin, H.; Gökçe, G.; Herrmann, B.
Abstract: Bycatch of rays and skates in towed fishing gears represents one of the major threats to these relatively slow-growing marine species. The objective of this study was to modify ground gear in a bottom trawl fishery to increase the escape of these species during towing without associated loss of target catch. Sea trials were carried out with a research vessel in Mersin Bay, North-eastern Mediterranean. Experimental ground gear was modified by cutting the rigging twine between the fishing line and the footrope in the central part of the ground gear. Capture of three unwanted bycatch species were estimated. The probability of capture of guitarfish ( Rhinobatos sp.) and common stingray ( Dasyatis pastinaca ) was significantly reduced to 8% and 20% for guitarfish and stingray, respectively compared to standard ground gear. The results for spiny butterfly ray ( Gymnura altavela ) were inconclusive due to the wide confidence intervals. Further, the catch comparison results for five out of six target species investigated did not show significant reduction in catch efficiency when using experimental gear compared to the standard trawl. Only for common sole ( Solea solea ) the modified trawl had significantly lower catch efficiency than the standard trawl. We believe that this technical measure for reducing unwanted bycatch in bottom trawls has a potential to be adopted by the fishery due to being an efficient, low-cost measure which does not create additional challenges during handling of the gear.